2019
DOI: 10.3390/cells8020087
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Ephexins in Physiology and Disease

Abstract: Dbl (B-cell lymphoma)-related guanine nucleotide exchange factors (GEFs), the largest family of GEFs, are directly responsible for the activation of Rho family GTPases and essential for a number of cellular events such as proliferation, differentiation and movement. The members of the Ephexin (Eph-interacting exchange protein) family, a subgroup of Dbl GEFs, initially were named for their interaction with Eph receptors and sequence homology with Ephexin1. Although the first Ephexin was identified about two dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 80 publications
(166 reference statements)
0
7
0
Order By: Relevance
“…Eph-interacting exchange protein (Ephexin) family RhoGEFs activate Rho GTPases, including RhoA, Rac, Cdc42, and RhoG (8). This family consists of five known members in most vertebrate species (Ephexin1 to -5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Eph-interacting exchange protein (Ephexin) family RhoGEFs activate Rho GTPases, including RhoA, Rac, Cdc42, and RhoG (8). This family consists of five known members in most vertebrate species (Ephexin1 to -5).…”
mentioning
confidence: 99%
“…This family consists of five known members in most vertebrate species (Ephexin1 to -5). A common feature of the Ephexin family proteins is that they all associate with and act downstream of Eph receptors, the largest subfamily of tyrosine kinase receptors that are activated by Ephrins and participate in various cellular processes (8)(9)(10)(11). Specifically, Ephexin1 (also known as NGEF or ARHGEF27) regulates axon growth cone dynamics and spine morphogenesis via binding to EphA4 and activation of RhoA (9,(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ephrin signaling plays a key role in cellular repulsion, attraction, and migration by controlling local cytoskeletal dynamics through Ephexin proteins and Rho GTPases 8,12 . Dysregulation of ARHGEF16 contributes to carcinogenesis and tumor progression 13,21 . However, how ARH-GEF16 is regulated in response to the progression of colon cancer remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…(ARHGEF5/TIM1), Ephexin4 (ARH GEF16), and Ephexin5 (ARHGEF15/Vsm-RhoGEF) 9,21,[29][30][31][32] . It has been reported that Ephexin1 and Ephexin5 are phosphorylated by Src or Eph receptors but not ARH-GEF16 21,29,33 . Here, we showed that FYN stabilized ARH-GEF16 by promoting ARHGEF16 phosphorylation in a manner dependent on FYN.…”
Section: Discussionmentioning
confidence: 99%